Psychological Framework of Early Emotional Bonds - Akram, Muhammad; Abbas, Sabahat; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
The attachment theory suggests that the parental-child relationship is the building block for future relationship patterns and immediate security and comfort. A securely attached child will likely have healthy relationships as an adult, with better emotional awareness, empathy, and capacity to create long-term love relationships. On the other hand, insecurely attached children may go on to experience issues with attachment into adulthood, leading to relationship difficulties, emotional dysregulation, and greater risk of mental health difficulties such as personality disorders, anxiety, and depression. Additionally, it has been proven that the attachment system itself is also dynamic and changes depending on a wide range of relational and environmental circumstances. The type of attachment relationships can be influenced by a variety of factors, such as parenting style, societal context, cultural expectations, and even the occurrence of outside stressors like trauma or divorce. For instance, therapies that foster secure attachment can effectively decrease the negative impacts of early trauma and adversity and allow children to be resilient.